Effect of Leverage, Profitability and Operating Capacity on Financial Distress in Manufacturing Companies Listed on The Indonesia Stock Exchange - Yolanda Effendy; Awaluddin Awaluddin; Loso Judijanto; Luckhy Natalia Anastasye Lotte; Al-Amin; Hadi Subeno (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to examine whether leverage, profitability and operating capacity affect financial distress in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2023. The data used is secondary data obtained from www.idx.co.id website. Determination of samples in research using porpusive sampling methods with special criteria. The results of the analysis are known to be a significant value of leverage of 0.000 < 0.05 with a calculation of -4.862 < table 1.992, so the variable leverage has a significant negative effect on financial distress conditions. The significant value on profitability is 0.000 < 0.05 with a count of 9,196 > table 1,992. So the probability variable has a significant positive effect on financial distress conditions. Significant value in Operating Capacity of 0.000 < 0.05 with a calculation of 8.422 > table 1.992, So operating capacity has a significant positive effect on financial distress.